Abundance of Plankton in the Waters of Geger Beach, Badung Regency, Bali - Vesensia, Octria; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
Geger Beach is located in Peminge traditional village area, Sawangan, Nusa Dua, Bali which is a tourism area and there is seaweed cultivation managed by local people. Such human activity will affect the quality of the waters which will result in an increase in nutrients and organic matter which can further lead to changes in the structure of plankton. The purpose of this study is to find out the types of plankton and the abundance of plankton found in the waters of Geger Beach using the pour method. This research was conducted in March 2021. Sampling is conducted once a week at three observation points. The total phytoplankton species obtained as many as 32 species consisting of 6 classes, namely Bacillariophyceae (23 genera), Xanthophyceae (1 genus), Cyanophyceae (3 genera), Ulvophyceae (1 genus), Conjugatophyceae or Zygnematophyceae (2 genera), Coscinodiscophyceae (2 genera). The dominant type of phytoplankton found during the study was the Gyrosigma fasciola species in the Bacillariophyceae class. Meanwhile, the total zooplankton obtained by 11 species consisting of 5 classes, namely Maxillopoda (3 genera), Hexanauplia (3 genera), Magnoliopsida , Branchiopoda, and Copepoda (1 genus). The dominant type of zooplankton found during the study was the Cyclops sp . species in the Maxillopoda class. The average abundance of phytoplankton is 120 cells/l, while the average abundance of zooplankton is 20 cells/l. The average diversity value of phytoplankton is 2,7, while the diversity of zooplankton is 1,4. The average dominance index value of phytoplankton is 0,06, while the average zooplankton dominance index is 0,25.